Comparison of the number and content of pathology laboratory samples before and after the COVID-19 pandemic - Parlak, Leymune; Tarini, Emine Zeynep (Polish Journal of Pathology, 2023)
Coronavirus disease 2019 (COVID-19) has caused respiratory system diseases and affected people’s access to healthcare services for diseases other than COVID-19. After the COVID-19 pandemic, changes occurred in the number and content of pathology laboratory samples, related to measures such as reducing the number of outpatient clinics in hospitals, postponing elective surgery, and restricting cancer screening. All samples sent to the pathology laboratory between 2019 and 2020 were included in our study. Biopsy, cytology, histochemical, and immunohistochemical staining and biopsies for malignant cases were evaluated. Changes in sample number and content caused by the pandemic were examined. The number of biopsies was 24 312 in 2019 and 13 208 in 2020. On comparison, a decrease was observed in all parameters. The largest (78.5%) and smallest (11.02%) decreases were observed in examinations of the incoming preparations for consultation (214–46) and Trucut needle biopsies (726–646), respectively. Cases such as appendectomies that require urgent intervention and malignancies that require further examination and diagnosis are the least affected. However, whether the decrease in cancer screening will affect the early diagnosis and treatment of malignancies and create a public health problem in the future remains to be established.